International liquidity, monetary spillovers and asset prices - Borja, Daniel Vincent (Philippine Management Review, 2011)
In this paper, we attempt to determine if international liquidity affects asset prices in three particular markets, namely : the United States (U.S.), the Euro area and the Asean (5 countries) region. Our study attempts to test whether there are monetary spillovers from one market to another that affect asset prices using quarterly data covering these markets from 1995 to 2005. We begin by finding an appropriate measure and definition for international liquidity. This definition is used to determine an appropriate variable that is combined with other control variables to form a regression equation for the real asset returns of the three particular markets. Based on our results, there is evidence that excess liquidity in the US and Euro area has a "push" effect on asset prices of both markets. We find that asset prices in the ASEAN 5 region are unaffected by international liquidity.